2012
DOI: 10.1055/s-0032-1316442
|View full text |Cite
|
Sign up to set email alerts
|

Breast-Feeding and Responses to Infant Vaccines: Constitutional and Environmental Factors

Abstract: Neonates and nursing infants are special with regard to immune development and vulnerability to infectious diseases. Although breast-feeding is essential to modulate and prime immune defenses, vaccines (an interventional prophylaxis) are crucial to prevent and control infectious diseases. During nursing, the type of feeding influences infants' natural defenses (including gut colonization) and their response to vaccines, both through cell-mediated immunity and specific antibody production. Given the variety and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 109 publications
(139 reference statements)
2
7
0
1
Order By: Relevance
“…A study carried out in Sweden indicates that children with exclusive breastfeeding for 90 days or more who had the Hib and pneumococcal vaccine, concurrently, obtained better serological protection when compared to children who were breastfed for a few days 21 . In this way, its corroborates that these practices carried out concomitantly, exclusive breastfeeding for six months and the fulfillment of the immunization schedule, could give a greater protection to children in this age group 7 , 21 .…”
Section: Discussionsupporting
confidence: 68%
“…A study carried out in Sweden indicates that children with exclusive breastfeeding for 90 days or more who had the Hib and pneumococcal vaccine, concurrently, obtained better serological protection when compared to children who were breastfed for a few days 21 . In this way, its corroborates that these practices carried out concomitantly, exclusive breastfeeding for six months and the fulfillment of the immunization schedule, could give a greater protection to children in this age group 7 , 21 .…”
Section: Discussionsupporting
confidence: 68%
“…Although breastfeeding is essential to modulate immune defences, vaccines are crucial to prevent infectious diseases. However, maternal factors related to breastmilk constituents and feeding practices can affect the response to vaccines [38]. A study by Dórea indicated that maternal constitutional and environmental factors and feeding practices can affect the response to vaccines.…”
Section: Maternal Vaccination Strengthens Breastmilk Immunitymentioning
confidence: 99%
“…A study by Dórea indicated that maternal constitutional and environmental factors and feeding practices can affect the response to vaccines. Sucklings without receiving the full benefit of breastfeeding could have altered immune responses affecting vaccine outcome [38]. The study concluded that vaccination practices should encourage the practice of exclusive breastfeeding [38].…”
Section: Maternal Vaccination Strengthens Breastmilk Immunitymentioning
confidence: 99%
“…Although the finding that longer breastfeeding is associated with a poorer response to BCG vaccination seems paradoxical, a significant literature supports the idea that the relationship between breastfeeding and vaccine responses is complex. For instance, studies have reported enhanced, decreased, or no difference in the immune response to some vaccinations, comparing breastfed to non-breastfed infants ( Dórea 2012 ). For BCG vaccines specifically, one study observed that breastfeeding enhanced lymphocyte blastogenesis (stimulated by purified protein derivative of Mycobacterium tuberculosis ) ( Pabst et al 1989 ), and a second study, that examined Mantoux test results at 6 months, found no difference in tuberculin response size across different strata of breastfeeding duration ( Goh et al 1989 ).…”
Section: Discussionmentioning
confidence: 99%